Feeding Preferences of Subterranean Termite Schedorhinotermes javanicus on Tusam (Pinus merkusii) Wood - Kutana, Agung Nugrawan; Nandika, Dodi; Arinana, Arinana (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Wood-destroying termites are quite influential in Indonesia, and the subterranean termite Schedorhinotermes javanicus is one of them. This study was conducted to determine the feeding preferences of subterranean termites S. javanicus on tusam (Pinus merkusii) wood and the influence of their environment. The bait woods made of tusam boards were installed at the experimental site. The weight loss and consumption of bait woods were studied with three test times (one, two, three) months of burial. The subterranean termite specimens attacking the bait woods, soil characteristics, and weather at the experimental field were also identified. The results demonstrated that the average air temperature at the experimental site was 25.4 ± 0.4°C, the average air humidity reached 88.8 ± 2.4%, and the light intensity at the experimental site ranged from 175.67 lux to 3889.7 lux. The results showed that S. javanicus quite actively attacked the bait wood. This can be seen from the high weight loss (35.03%) and the wood consumption (38.78 g). The weight loss after three exposure times in the experimental field was up to 13.54%, 16.38%, and 35.03%, respectively. The wood consumption during the same experimental period reached 14.9 g, 18.25 g, and 38.78 g, sequentially. The high weight loss and the consumption of bait wood indicate the high feeding preference of the subterranean termites S. javanicus on tusam wood. Keywords: field test, Pinus merkusii, Schedorhinotermes javanicus, weight loss, wood consumption